1997
DOI: 10.1152/jn.1997.78.5.2309
|View full text |Cite
|
Sign up to set email alerts
|

Three Kinetically Distinct Ca2+-Independent Depolarization-Activated K+ Currents in Callosal-Projecting Rat Visual Cortical Neurons

Abstract: Three kinetically distinct Ca 2+ -independent depolarization-activated K + currents in callosalprojecting rat visual cortical neurons. J. Neurophysiol. 78: 2309Neurophysiol. 78: -2320Neurophysiol. 78: , 1997. Whole cell, Ca 2+ -independent, depolarization-activated K + currents were characterized in identified callosalprojecting (CP) neurons isolated from postnatal day 7-16 rat primary visual cortex. CP neurons were identified in vitro after in vivo retrograde labeling with fluorescently tagged latex microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
38
2

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 35 publications
13
38
2
Order By: Relevance
“…2C). These results are consistent with those in other mammalian neurons showing low sensitivity of somatodendritic A-type potassium current to external TEA and moderate sensitivity to 4-AP (Segal et al, 1984;Huguenard et al, 1991;Bouskila and Dudek, 1995;Klee et al, 1995;Locke et al, 1997;Song et al, 1998). The high TEA sensitivity of the steadystate current activated by stronger depolarizations suggests that this component of current originates from different channel types than those underlying the transient current.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…2C). These results are consistent with those in other mammalian neurons showing low sensitivity of somatodendritic A-type potassium current to external TEA and moderate sensitivity to 4-AP (Segal et al, 1984;Huguenard et al, 1991;Bouskila and Dudek, 1995;Klee et al, 1995;Locke et al, 1997;Song et al, 1998). The high TEA sensitivity of the steadystate current activated by stronger depolarizations suggests that this component of current originates from different channel types than those underlying the transient current.…”
Section: Resultssupporting
confidence: 91%
“…Somatodendritic I A is often distinguished from other components of potassium current by its pharmacology. Somatodendritic I A is relatively resistant to external tetraethylammonium (TEA) (half-block, Ͼ100 mM) and moderately sensitive to 4-aminopyridine (4-AP) with a typical half-blocking concentration of ϳ1 mM (Segal et al, 1984;Zbicz and Weight, 1985;Huguenard et al, 1991;Klee et al, 1995;Locke et al, 1997;Song et al, 1998) (for review, see Song, 2002;Jerng et al, 2004b). Thus, the functional roles of I A are often studied by examining the effect of 3-10 mM 4-AP.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported 4-aminopyridine-sensitive currents in rat neocortical pyramidal cells (see ref. 33 and citations therein). Consistent with these studies, in our preparation, application of 4-aminopyridine (100 M) reduced a depolarization-activated hyperpolarizing current (n ϭ 2).…”
Section: Resultsmentioning
confidence: 99%
“…In hippocampal interneurons, MPOs are prevented by Ba 2ϩ and 4-aminopyridine (4-AP) but not by tetraethylammonium (TEA) (Chapman and Lacaille, 1999a). This pharmacological profile suggests that transient A-type K ϩ currents or dendrotoxinsensitive K ϩ currents (I D ) may be involved in MPO generation (Rudy, 1988;Hurst et al 1995;Locke and Nerbonne, 1997;Coetzee et al 1999;Shi et al 2000). Activation of MPOs at subthreshold membrane potentials (Chapman and Lacaille, 1999a) is also consistent with a potentially important role of these currents (Coetzee et al, 1999;Lien et al, 2002).…”
Section: Introductionmentioning
confidence: 81%